Advance directives in European long-term care facilities: a cross-sectional survey. Issue Volume 12:Issue e3(2022) (21st May 2019) - Andreasen, Paula; Finne-Soveri, Ulla Harriet; Deliens, Luc; Van den Block, Lieve; Payne, Sheila; Gambassi, Giovanni; Onwuteaka-Philipsen, Bregje D; Smets, Tinne; Lilja, Eero; Kijowska, Violetta; Szczerbińska, Katarzyna
Abstract : Background: End-of-life care practices in long-term care facilities (LTCFs) are the focus of growing attention in Europe, due to rapidly increasing number of older persons living in LTCFs. The knowledge about end-of-life discussions or existence of written advance directives in the European LTCFs is scarce. This study's aim is to investigate the prevalence of written advance directives and their sociodemographic associates, among recently deceased LTCF residents, in six European countries. Methods: Data from the European Union-funded PACE database were collected from 322 LTCFs in six European countries in 2014. The assessments were performed by using two questionnaires designed for LTCF administrative staff and for staff member. LTCFs were selected within each country by using proportional stratified random sampling procedure. Facilities with certain types and sizes were included from each country. Multilevel multivariate analyses were performed to evaluate associations between written advance directives and selected predictors. Results: In total, 32.5 % of the 1384 deceased LTCF residents had a written advance directive with a range from 0% to 77 % between countries. The proportion of the most common advance directive, 'Do not resuscitate in case of cardiac or respiratory arrest (DNR)', varied correspondingly from 0% to 75%. LTCF type (OR 2.86 95% CI 1.59 to 5.23) and capability of expressing at the time of admission (OR 3.26 95% CI 2.26 to 4.71) were the independent predictors for advance directive. Residents living in LTCFs where physician was available were less likely to have advance directive compared with residents from LTCFs where physician was not available. Conclusion: Extensive differences for prevalence of written advance directive exist between countries among older LTCF residents in Europe. Timely and appropriate response to LTCF resident's health needs and preferences efforts advance care planning.